Correlation between Latin American And Caribbean Journals Impact Indicators - Costa, Heloisa; Canto, Fabio Lorensi do; Pinto, Adilson Luiz; Talau, Marcos (Bibliotecas. Anales de investigación, 2023)
Purpose – Identify the levels of correlation between impact indicators from Latin American and Caribbean journals indexed in databases.The selected indicators are the Impact Factor, 5-year Impact Factor, EigenFactor Score, Article Influence Score, Journal Citation Indicator, SJR, CiteScore, h-index (SJR), Source-normalized Impact per Paper, and h5-index Design/methodology/approach – Data were downloaded from Journal Citation Reports, SCimago, and Scopus. A Phyton script was used to search for journals titles and extract the h5-indexfrom Google Scholar Metrics. Pearson and Spearman coefficients tests were used to identify the level of correlation between pairs of indicators from the same set of journals. Data are analyzed in general, and according to the areas of Science, Technology and Medicine, and Arts, Humanities and Social Sciences. Findings – The correlation coefficients are positive moderate (0.40 < 0.69) and strong (0.70 < 0.89) in most pairings, with a very strong level (> 0.90) between Impact Factor, 5-year Impact Factor, and CiteScore (CS),Science, Technology and Medicine journals have stronger correlation levels than Arts, Humanities and Social Sciences journals. Considering the relationship between availability and average correlation, the CS and the h5-index are the most suitable indicators for journals assessment in the region. Originality/value – This paper provides a correlation analysis between impact indicators of all indexed Latin American and Caribbean journals. It is also innovative by using an automated technique of search and data extraction in Google Scholar Metrics.The results can contributeto the elaboration of journals evaluation policies in the countries of the region.